Affect of Six Sigma Methdology on Reliability and Quality of Product - Shashvat, Kumar; Kaur, Arshpreet; Chadha, Raman (International Journal of Computer Sciences and Engineering, 2025)
Six Sigma at various esteemed organizations merely means a calculation of excellence that strives for near perfection. Six Sigma is a restricted, data-driven move toward methodology for eliminating defects in any process – from developed to transactional and from manufactured goods to service. The statistical representation of Six Sigma describes quantitatively of how a procedure is performed. To attain Six Sigma, a process must not produce more than 3.4 defects per million opportunities. A Six Sigma defect is distinct, no matter at which peripheral of customer stipulation it occurs. A Six Sigma prospect is entire extent of probability for a defect. Six Sigma calculator can be used to design process sigma. Following paper works on different approaches of Six Sigma such as Lean Six Sigma, how it affects the overall customer experience, work and effort when put together in a process. It studies of how Lean and Six Sigma supplement each other and their use at different levels of organization. It focuses on how use of six sigma approach affects reliability; different reliability metrics on which reliability has been measured upon in past and changes which six sigma has induced in. Its overall effect on the working of an organization process and number of failures faced when it is implemented thoroughly.